Pengaruh Olahan Daun Kelor Terhadap Peningkatan Status Gizi Pada Balita Stunting: Literature Review - Novianti, Irgiani Fitri; Purnamawati, IGA Dewi (Maternal & Neonatal Health Journal, 2025)
Stunting occurs when a child under five years of age has a height that is shorter than expected for their age, or falls below two standard deviations from the average growth of children. This condition is closely related to nutritional status, which reflects the balance between the body’s nutrient requirements and the nutrient intake obtained from food. One highly nutritious local food source is the moringa plant, particularly its edible leaves. In 100 grams of dried moringa leaves, there are 27.1 grams of protein and 28.2 grams of iron, indicating strong potential to support nutritional improvement in children. This review aims to determine the effect of processed moringa leaves on improving the nutritional status of stunted under-five children. The literature search was conducted through Google Scholar using a literature review method involving five articles. The findings show that processed moringa leaves are proven to improve the nutritional status of stunted children. Therefore, with this evidence, it is expected that practitioners can recommend complementary feeding for breastfeeding (CF) or additional foods made from moringa leaves as one strategy to address nutritional problems in stunted children.